Feasibility of corporate voluntary arrangement ("CVA") in solving insolvency issues in abandoned housing projects: a comparative legal analysis between Malaysia and the United Kingdom - Md Dahlan, Nuarrual Hilal (Sweet & Maxwell Asia, 2014)
The Malaysian Corporate Law Reform Committee ("CLRC") was established among others to review the provisions under the Companies Act 1965 (Act 165) and recommend to the Malaysian government new corporate laws to accelerate the due development of the Malaysian corporate sector. CLRC has conducted research in to the current provisions under the Companies Act 1965 since December 2003 which took about four years to complete.The result is the Final Report of the CLRC. Under this report, the CLRC has recommended the establishment of a Corporate Voluntary Arrangement ("CVA") to take over the affairs of insolvent companies and rescue them.This paper is a result of a pure legal research that relates to abandoned housing projects in Malaysia.The authors also analysed the CVA's provisions vis-a-vis the insolvency issues in abandoned housing projects in Malaysia. The objective of this paper is to study the feasibility of the establishment and powers of the CVA in dealing with the insolvency issues in abandoned housing projects and in protecting the rights of the purchasers.Through this writing, the authors are of the view that, the recommendation of the CLRC for the establishment of CVA is commendable. Nonetheless, it is submitted that, in the case of abandoned housing projects, despite having statutory and legal powers, the proposed CVA still cannot fully provide a comprehensive solution in dealing with the insolvency issues in abandoned housing projects, let alone protect the purchasers' interests.A comparative legal analysis with the United Kingdom's Company Voluntary Arrangement ("UK CVA") is also done to find out any lessons and advantages that the UK CVA may have in the face of insolvency issues in abandoned housing projects.This paper suggests certain legal approaches to improve the rehabilitation mechanism of abandoned housing projects purportedly to be carried out through CVA and for protecting the rights and interests of the stakeholders.